Elephants behavior and conservation - de Silva, Shermin R. (Cambridge University Press, 2025)
This volume compiles more than twenty years of behavioral research on the three living species of elephants in Africa and Asia (African Savannah, African Forest, and Asian elephant), together with their implications for conserving and managing wild elephant populations. The theoretical background, key terminology and findings are explained and presented in engaging language accessible to a wide range of non-specialists, from students to seasoned professionals. By viewing data from numerous studies through a comparative evolutionary perspective, the similarities and distinctions among species and populations come into clear relief, providing insight into the complexities of protecting these charismatic yet highly threatened mega-herbivores. Rather than mere exposition of what is known, readers are invited to reflect on the additional questions and puzzles that are still in need of answers, in the hope of inspiring a new generation of researchers and conservationists